A major choice: exploring the factors influencing undergraduate choices of Communication major. Issue 2 (1st December 2017) - Mishra, Naveen; Ismail, Abduraoof Ahmed; Al Hadabi, Sanaa Juma
Abstract : This study explores the reasons behind the popularity of majoring in Public Relations as opposed to Journalism or Digital Media among mass communications undergraduates in Oman. It attempts to gain insight into the factors influencing students' decision-making process in selecting their major. It explores factors such as choice of major and sources of information that shape students' knowledge and perception of the majors, using variables such as knowledge of job market, knowledge of curriculum, information sources and personal influences shaping major choice and selection. The study confirms that perception of the job market is a crucial factor in the selection of the majors. It also reveals that family plays a crucial role in influencing students' decision-making process while choosing a major. The study concludes that strengthening the role of the academic advisor and educating students on course content and learning outcomes can increase the acceptance of less popular majors among communication undergraduates. The study is relevant in the context that the falling numbers of student enrolments in some areas of media studies could lead to a decline in teaching and research activities in those areas, in addition to a possible shortfall of specific skilled professionals in the national labour market pool.